Preparation of thick silica coatings on carbon fibers with fine-structured silica nanotubes induced by a self-assembly process - Baumgärtner, Benjamin; Möller, Hendrik; Neumann, Thomas; Volkmer, Dirk (Beilstein Journal of Nanotechnology, 2017)
A facile method to coat carbon fibers with a silica shell is presented in this work. By immobilizing linear polyamines on the carbon fiber surface, the high catalytic activity of polyamines in the sol–gel-processing of silica precursors is used to deposit a silica coating directly on the fiber’s surface. The surface localization of the catalyst is achieved either by attaching short-chain polyamines (e.g., tetraethylenepentamine) via covalent bonds to the carbon fiber surface or by depositing long-chain polyamines (e.g., linear poly(ethylenimine)) on the carbon fiber by weak non-covalent bonding. The long-chain polyamine self-assembles onto the carbon fiber substrate in the form of nanoscopic crystallites, which serve as a template for the subsequent silica deposition. The silicification at close to neutral pH is spatially restricted to the localized polyamine and consequently to the fiber surface. In case of the linear poly(ethylenimine), silica shells of several micrometers in thickness can be obtained and their morphology is easily controlled by a considerable number of synthesis parameters. A unique feature is the hierarchical biomimetic structure of the silica coating which surrounds the embedded carbon fiber by fibrillar and interconnected silica fine-structures. The high surface area of the nanostructured composite fiber may be exploited for catalytic applications and adsorption purposes.
Keywords: biomimetic silicification; carbon fiber; self-assembly; silica nanotubes; sol–gel process